Managing with the power of NLP : neurolinguistic programming, a model for better management - Molden, David (Pearson Education, 2007)
"This is a 'must have' book for any leader interested in improving their capabilities in engaging with people, teambuilding and managing change. David's alchemy is to mix traditional NLP, his love of eastern philosophy and his own business experience. There is one clear message that underpins this book: your unlimited potential is within reach now." David R. Steele, Managing Director, International Paper Ireland "Finally we have a book written by a master of both NLP and management. This book decodes the jargon of NLP for the manager and shows how this powerful technology can make managers more effective and productive and businesses more profitable." Wyatt Woodsmall PhD, The National Training Institute for NLP "This incredibly valuable contribution ... has an amazing array of essential topics with plenty of practical examples and applications of NLP to management and business." Marvin Oka, NLP Master Trainer, The International NLP Trainers Association NLP is a powerful tool -- if you know how to use it. It can be used to enhance many aspects of performance, from decision making and communication, to strategic planning and creative thinking. For this very reason, NLP is crucial to all managers and leaders, yet many of us are still unfamiliar with its uses and benefits. Now in its second edition, this bestselling book is specifically designed to help you learn how to apply NLP to many aspects of management. Background, concepts and techniques are all included, along with practical exercises to ensure you get a thorough grounding and understanding. Completely revised and updated, and packed full of even more practical exercises, Managing With the Power of NLP is your means to achieving greater management success